Comparison of Different In Vivo Animal Models of Brachial Plexus Avulsion and Its Application in Pain Study. (12th November 2020) - Xian, Hang; Xie, Rougang; Luo, Ceng; Cong, Rui
Abstract : Brachial plexus injuries (BPIs) are high-energy trauma that can result in serious functional problems in the affected upper extremities, and brachial plexus avulsion (BPA) could be considered the most severe type of them. The booming occurrence rate of BPA brings up devastating impact on patients' life. Complications of muscle atrophy, neuropathic pain, and denervation-associated psychological disorders are major challenges in the treatment of BPA. Animal models of BPA are good vehicles for this kind of research. Full understanding of the current in vivo BPA models, which could be classified into anterior approach avulsion, posterior approach avulsion, and closed approach avulsion groups, could help researchers select the appropriate type of models for their studies. Each group of the BPA model has its distinct merits and demerits. An ideal BPA model that can inherit the advantages and make up for the disadvantages is still required for further exploration.